STRATEGI KOMUNIKASI PEMASARAN DIAN PELANGI CABANG PEKANBARU DALAM MEMPERTAHANKAN LOYALITAS PELANGGAN - Mutia, Ade; Lubis, Evawani Elysa (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
Marketing communication strategy is important in marketing because can make effective marketing. Company Dian Pelangi is a company engaged in retail. As one of the leading fashion houses in Indonesia, Dian Pelangi have a competitor that run in the same type and the company need a strategy to get the aim of the company. Because of that the researcher was interest to do this research with the aim to know marketing communication strategy Dian Pelangi Pekanbaru branch in maintaining customer loyalty.This research uses qualitative methods, namely the collection of data obtained based on the fact data in the field through observations, interviews, and documentation. The subjects in this research is 2 manager and 7 loyal customers Dian Pelangi Pekanbaru branch are selected using purposive technique. This research uses an interactive data analysis techniques, for data validity checking techniques through the extension of participation, increase persistence, and triangulation.The goal of research shows that the marketing communication strategy Dian Pelangi Pekanbaru branch in maintaining customer loyalty do by segmentation, targeting, positioning, promotional mix consists of advertising, sales promotion, personal selling, direct marketing, publicity, public relations, and word of mouth communication.Keywords: Marketing Communication Strategy, Customer Loyalty